Percutaneous transluminal angioplasty in renovascular hypertension - Stríbrná, J; Belán, A; Veselá, M; Vojtísková, H; Karasová, M (Cor et vasa, 1985)
The results of percutaneous transluminal angioplasty of renal arteries (PTA) were evaluated in 43 patients followed up for 2-39 months (mean: 14 months). The benefit of PTA was higher (82%) in hypertensives with arterial fibrodysplasia (n = 11) than in atherosclerotic vascular lesions (53%, n = 19). Of 15 patients with reduced renal function before PTA, the glomerular filtration rate rose in seven. A major complication was in one patient arterial dissection and in another one loss of function of the transplanted kidney due to acute tubular necrosis. The results confirm that PTA is an important contribution to the treatment of renovascular hypertension.
Keywords: Arteriosclerosis; Follow-Up Studies; Urography; Angioplasty, Balloon; lidé; Humans; urografie; krevní tlak; následné studie; balónková angioplastika; hodnoty glomerulární filtrace; renovaskulární hypertenze; lidé středního věku; Glomerular Filtration Rate; Middle Aged; stenóza; Female; Male; arterioskleróza; Adult; Constriction, Pathologic; mužské pohlaví; Aged; Hypertension, Renovascular; ženské pohlaví; dospělí; Blood Pressure; senioři